Management of acute respiratory distress syndrome in a French Bulldog using airway pressure release ventilation. (15th July 2013) - Sabino, Catherine V.; Holowaychuk, Marie; Bateman, Shane
Abstract: Objective: To describe the successful clinical management of a dog with acute respiratory distress syndrome (ARDS) using airway pressure release ventilation (APRV). Case Summary: An 18‐month‐old female French Bulldog was presented for routine ovariohysterectomy and correction of brachycephalic airway obstruction syndrome. Following the surgical procedures, the dog developed aspiration pneumonia and ARDS. Her clinical condition failed to improve with conventional pressure‐support mechanical ventilation and she was subsequently managed with APRV. She recovered fully and exhibited no clinical or radiographic abnormalities during follow‐up examinations. New or Unique Information Provided: This is the first reported use of APRV to manage refractory hypoxemia associated with ARDS in a dog. This alternative mode of mechanical ventilation can be considered a feasible alternative in canine patients with ARDS.